Analysis of Frieze Patterns Concepts in Pua Kumbu - Liyana, Truna; Noria, Tugang; Norhunaini, Mohd Shaipullah; Nur Rasfina, Mahyan (Aliva Global Research and Development, 2021)
A traditional practice of the Iban from Sarawak, Pua Kumbu is a form of textile which is famous for its beauty. There is a general appreciation of how it is exquisitely designed and patterned. It has been recognised by analytical studies that Pua Kumbu designs use transformational geometrical shapes in the frieze. This paper explores the geometry elements that have been portrayed in the form of different flora and fauna motifs. The examples of mathematical ideas in motifs produced by weavers in Sarawak have been analysed through this study. Although it is still in the form of preliminary observations, it has been revealed that the principles of geometry, such as enlargement, reflection, rotation, and translation are often used in the Pua Kumbu patterns. This woven art by the Ibans indirectly applies the principles of geometry in the form of beautiful and high-value motifs. This paper may benefit this field and the professionals related to it to act as a useful guideand also may serve as a point of reference for future studies on the unique patterns and designs of Pua Kumbu. The study also suggests that patterns based on geometry and symmetry exist in the ways Pua Kumbu is created.